2022
DOI: 10.26633/rpsp.2022.67
|View full text |Cite
|
Sign up to set email alerts
|

Productos procesados y ultraprocesados y su relación con la calidad de la dieta en niños

Abstract: Objetivo. Estimar el efecto que representa en la calidad de la dieta de la primera infancia uruguaya —niños de 2 a 4 años— el consumo de productos que contienen cantidades excesivas de nutrientes críticos asociados a las enfermedades no transmisibles (ENT) (azúcares libres, grasas totales, grasas saturadas y sodio), según el modelo de perfil de nutrientes de la Organización Panamericana de la Salud (OPS). Métodos. Se utilizó un recordatorio de ingesta de alimentos durante 24 horas en una muestra representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Compared to people with lower UPF intake, people who consume more UPFs were found to have poorer quality diets, characterized by higher intakes of energy and nutrients, such as total fat, saturated fat, trans fat, and free sugars, as well as lower intakes of protein, fiber, vitamins A, C, D, B6, and B12, and minerals, such as zinc, iron, calcium, magnesium, phosphorus, and potassium. [6][7][8][9][10][11][12][13][14][15][16][17] Similarly, a randomized controlled clinical trial comparing the effects on energy intake of an ultra-processed diet to an unprocessed diet showed that energy, carbohydrate, and fat intake were 25% higher on average in the ultraprocessed diet, while protein intake was lower. 18 Longitudinal studies further showed that subjects with a higher intake of UPFs have a higher risk of developing obesity, 19 type 2 diabetes, 20 cancer, 21 cardiovascular disease, 22 hypertension, 23 metabolic syndrome, and double-burden malnutrition in children and adolescents, 24,25 as well as all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to people with lower UPF intake, people who consume more UPFs were found to have poorer quality diets, characterized by higher intakes of energy and nutrients, such as total fat, saturated fat, trans fat, and free sugars, as well as lower intakes of protein, fiber, vitamins A, C, D, B6, and B12, and minerals, such as zinc, iron, calcium, magnesium, phosphorus, and potassium. [6][7][8][9][10][11][12][13][14][15][16][17] Similarly, a randomized controlled clinical trial comparing the effects on energy intake of an ultra-processed diet to an unprocessed diet showed that energy, carbohydrate, and fat intake were 25% higher on average in the ultraprocessed diet, while protein intake was lower. 18 Longitudinal studies further showed that subjects with a higher intake of UPFs have a higher risk of developing obesity, 19 type 2 diabetes, 20 cancer, 21 cardiovascular disease, 22 hypertension, 23 metabolic syndrome, and double-burden malnutrition in children and adolescents, 24,25 as well as all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding edible products that belong to the category of UPFs, evidence from different countries has shown that they are high in ingredients that present health risks and low in protective nutrients. Compared to people with lower UPF intake, people who consume more UPFs were found to have poorer quality diets, characterized by higher intakes of energy and nutrients, such as total fat, saturated fat, trans fat, and free sugars, as well as lower intakes of protein, fiber, vitamins A, C, D, B6, and B12, and minerals, such as zinc, iron, calcium, magnesium, phosphorus, and potassium 6–17 . Similarly, a randomized controlled clinical trial comparing the effects on energy intake of an ultra‐processed diet to an unprocessed diet showed that energy, carbohydrate, and fat intake were 25% higher on average in the ultra‐processed diet, while protein intake was lower 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, se ha demostrado que el consumo de alimentos procesados y ultraprocesados posee una relación directa con el desbalance de la ingesta de nutrientes; además, se ha observado que dichos alimentos causan obesidad, hipertensión arterial, diabetes, cáncer y dislipemias, a la vez que disminuyen las defensas del cuerpo, ya que carecen de nutrientes protectores de la salud (Berón et al, 2022). El desarrollo de dichas enfermedades se debe a que los alimentos procesados y ultraprocesados tienen una baja calidad nutricional porque poseen altos nivel de grasas saturadas, azúcares libres y sal, pero muy pocas proteínas, Consumo de Alimentos Procesados y su Repercusión en la Salud Infantil desarrollo; al contrario, solo actúan como detonantes de diversas enfermedades, principalmente, obesidad, sobrepeso y problemas cardiovasculares.…”
Section: Consumo De Alimentos Procesados Y Su Repercusión En La Salud...unclassified